LITERACY POWER OPENS ACCESS TO ALL STUDENTS AND EMPOWERS FEMALE STUDENTS: A SOUTH AUSTRALIAN SCHOOL GEOGRAPHY CASE STUDY - Andy, Andy (Jurnal Inspirasi, 2014)
Educators and governments need to regard and encourage more access to literacy genres. By being able to access to multiple genres of literacy, students are empowered to perform better in tests, which in the long run, enables them to take control of their own world and future. In addition, policy makersâ consideration also needs to be equally addressed to both sexes: females and males. They should not get marginalised, either their preference or their interest. In the case of Â South Australian school geography, the girls are believed to be marginalised in both their preference and interest. In 1991, there was âan unusually high number of girlsâ failed PES geography examination, the rationale is believed that there was unbalanced address to female and male students in the examination that the guestions are gendered in a way that it is to marginalize feminist and consider masculine as superior. Â Keywords: access, literacy, gendered questions, school geography